Friction material, brake friction pad and preparation method thereof, brake friction pair

By using friction materials prepared by a variety of metal and inorganic vibration-absorbing materials, the noise and vibration problems generated by carbon ceramic coating brake discs during the brake process are solved, and the effects of vibration reduction, noise reduction and high-temperature stable friction coefficient are achieved.

CN119187555BActive Publication Date: 2025-03-07HUNAN JINLI HIGH TECH CO LTD

Patent Information

Application Number
CN202411688043.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

Carbon ceramic coated brake discs are prone to frictional vibration during the brake process, resulting in brake noise and affecting ride comfort.

Method used

Braking friction brake pads are prepared by hot press molding and curing treatment using friction materials including metal vibration-absorbing materials such as chromium steel alloy, manganese copper alloy and cast iron alloy, as well as inorganic vibration-absorbing materials such as vermiculite and porous graphite.

Benefits of technology

It effectively reduces brake noise and vibration, improves ride comfort, and maintains the friction coefficient stable under high temperature conditions, avoiding heat fading.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application provides a friction material, a brake friction pad and a preparation method thereof, and a brake friction pair. The friction material includes the following components: 20% to 60% of a first damping material, 8% to 29% of a second damping material, 10% to 20% of an adhesive, 3% to 15% of spherical alumina, 3% to 20% of zirconium silicate, 3% to 10% of stannous sulfide, and 3% to 15% of chromite; wherein the first damping material includes a chrome steel alloy, a manganese copper alloy, and a cast iron alloy; and the second damping material includes vermiculite and porous graphite. The present application uses a first damping material with an excellent attenuation coefficient and an inorganic second material with a porous structure to prepare a friction material; the first damping material can convert external mechanical vibration energy into internal friction heat energy, thereby reducing vibration intensity; the porous structure of the second damping material can absorb and reduce the transmission of brake vibration energy, thereby reducing brake vibration and noise.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of friction materials, and in particular to a friction material, a brake friction pad and a preparation method thereof, and a brake friction pair. Background Art

[0002] Carbon ceramic coated brake discs are made of a composite of carbon / carbon matrix and silicon carbide brake coating, and have the advantages of low density, light weight, high temperature resistance, wear resistance, and no rust. Compared with traditional cast iron brake discs, carbon ceramic coated brake discs can effectively increase the cruising range of new energy vehicles, improve the safety factor of emergency braking and long downhill braking at high temperatures, reduce the maintenance frequency of brake discs, reduce maintenance costs, and reduce the rust and adhesion problems of vehicles in humid and salt spray environments. It is hailed as the first choice for new energy vehicles. The new generation of brake discs.

[0003] The carbon / carbon matrix in the carbon-ceramic coated brake disc mainly plays a supporting role, and the dense silicon carbide surface layer mainly plays a friction role. Due to the high hardness of the dense silicon carbide layer, compared with the cast iron brake disc, under the same braking energy and friction torque, the carbon-ceramic coated brake disc and the traditional brake friction brake pad are more likely to generate friction vibration during braking, thereby causing brake noise, resulting in discomfort during riding and braking.

[0004] Therefore, the traditional technology still needs to be improved. Summary of the invention

[0005] Based on this, one or more embodiments of the present application provide a friction material, a brake friction pad and a preparation method thereof, and a brake friction pair that can reduce vibration and noise and have a stable friction coefficient.

[0006] According to a first aspect of an embodiment of the present application, a friction material is provided, comprising the following components, measured by mass percentage: 20% to 60% of a first vibration damping material, 8% to 29% of a second vibration damping material, 10% to 20% of an adhesive, 3% to 15% of spherical alumina, 3% to 20% of zirconium silicate, 3% to 10% of stannous sulfide, and 3% to 15% of chromite;

[0007] The first vibration-damping material includes chrome steel alloy, manganese copper alloy and cast iron alloy; the second vibration-damping material includes vermiculite and porous graphite.

[0008] In one embodiment, based on the total mass of the friction material, the first vibration damping material includes 10% to 30% of chrome steel alloy, 5% to 20% of manganese copper alloy and 5% to 25% of cast iron alloy.

[0009] In one embodiment, based on the total mass of the friction material, the second vibration damping material includes 3% to 9% vermiculite and 5% to 20% porous graphite.

[0010] In one embodiment, the friction material satisfies at least one of the following characteristics:

[0011] (1) The mass percentage of chromium in the chromium steel alloy is 10% to 15%, and the mass percentage of carbon is 0.05% to 0.55%;

[0012] (2) The chrome steel alloy comprises one or more of chrome steel alloy fibers and chrome steel alloy powders; the length of the chrome steel alloy fibers is 2 mm to 10 mm, and the particle size of the chrome steel alloy powder is 0.01 mm to 2 mm;

[0013] (3) The mass percentage of manganese element in the manganese-copper alloy is 40% to 80%;

[0014] (4) The manganese-copper alloy comprises one or more of manganese-copper alloy fibers and manganese-copper alloy powders; the length of the manganese-copper alloy fibers is 2 mm to 10 mm, and the particle size of the manganese-copper alloy powder is 0.01 mm to 2 mm;

[0015] (5) The mass percentage of carbon element in the cast iron alloy is 2.5% to 4.5%;

[0016] (6) The cast iron alloy comprises one or more of cast iron alloy fibers and cast iron alloy powders; the length of the cast iron alloy fibers is 2 mm to 10 mm, and the particle size of the cast iron alloy powder is 0.01 mm to 2 mm.

[0017] In one embodiment, the friction material satisfies at least one of the following characteristics:

[0018] (1) The particle size of the spherical alumina is 0.005 mm to 0.03 mm;

[0019] (2) The particle size of the zirconium silicate is 0.01 mm to 0.04 mm;

[0020] (3) The particle size of the stannous sulfide is 0.01 mm to 0.061 mm;

[0021] (4) The particle size of the chromite is 0.019 mm to 0.089 mm;

[0022] (5) The particle size of the vermiculite is 0.15 mm to 4 mm;

[0023] (6) The particle size of the porous graphite is 0.038 mm to 0.5 mm.

[0024] In one embodiment, the adhesive includes one or more of phenolic resin, rubber-modified phenolic resin, phosphorus-modified phenolic resin, silicon-modified phenolic resin and cashew nut shell oil-modified phenolic resin.

[0025] A brake friction pad comprises the above-mentioned friction material.

[0026] A method for preparing a friction brake pad comprises the following steps:

[0027] Providing various raw materials according to the above-mentioned components of the friction material, mixing them, and obtaining a mixed material;

[0028] The mixed material is stacked with a steel backing, and a brake pad blank is obtained by hot pressing;

[0029] The brake pad blank is subjected to curing treatment, shape processing treatment and assembly treatment in sequence to obtain a brake friction brake pad.

[0030] In one embodiment, the preparation method satisfies at least one of the following characteristics:

[0031] (1) The pressing pressure per unit area of ​​hot pressing is 15MPa~60MPa;

[0032] (2) The temperature of hot pressing is 140℃~170℃;

[0033] (3) The curing temperature is 200℃~240℃ and the curing time is 9h~11h.

[0034] A brake friction pair comprises the above-mentioned brake friction brake pad and a silicon carbide coated brake disc.

[0035] Compared with the traditional technology, this application has the following beneficial effects:

[0036] The present application adopts metal vibration-damping materials with excellent attenuation coefficients and inorganic vibration-damping materials with porous structures to prepare friction materials; metal vibration-damping materials can convert external mechanical vibration energy into internal friction heat energy, thereby reducing vibration intensity; the porous structure of inorganic vibration-damping materials can absorb and reduce the transmission of brake vibration energy, thereby reducing brake vibration and noise.

[0037] In addition, during the heat treatment process, the porous structure of the inorganic vibration damping material can absorb the small molecular products produced by the thermal decomposition of the resin, preventing thermal decay and thus maintaining a stable friction coefficient. DETAILED DESCRIPTION

[0038] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.

[0040] In the present application, "plurality", "multiple", "multiple times", "multiples", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0041] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0042] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0043] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1-10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.

[0044] Some embodiments of the present application provide a friction material, comprising the following components, measured by mass percentage: 20% to 60% of a first vibration damping material, 8% to 29% of a second vibration damping material, 10% to 20% of an adhesive, 3% to 15% of spherical alumina, 3% to 20% of zirconium silicate, 3% to 10% of stannous sulfide, and 3% to 15% of chromite;

[0045] The first vibration-damping material includes chrome steel alloy, manganese copper alloy and cast iron alloy; the second vibration-damping material includes vermiculite and porous graphite.

[0046] The raw materials of the friction material of the present application include three kinds of metal vibration-damping materials, namely chromium steel alloy, manganese copper alloy and cast iron alloy, and two kinds of inorganic vibration-damping materials, namely vermiculite and porous graphite. The above-mentioned vibration-damping materials cooperate and work synergistically with each other, so that the prepared friction material can have both vibration-damping and noise-reducing effects.

[0047] The present application adds spherical aluminum oxide, zirconium silicate and chromite to the raw material components of the friction material, which can increase the friction coefficient of the friction material. In the conventional technology, oxides or silicates with a Mohs hardness greater than 5 such as silicon carbide and zirconium oxide are used to increase the friction coefficient, but the above materials may cause excessive wear and noise of the friction material. Stannous sulfate and chromite are friction mitigation materials; among them, stannous sulfate is a layered material, and the slip of the material crystal interface and the active sulfur atoms decomposed at high temperature can mitigate severe friction, thereby reducing friction loss.

[0048] The metal materials used to prepare friction materials in traditional technology include steel fibers, copper fibers, brass fibers and their powders. The above materials can be used as reinforcing fibers to increase the strength of friction materials, and can also be used as heat-conducting materials to increase the service life of friction materials. The first vibration-damping material of the present application not only has the above-mentioned functions of increasing strength and improving service life, but also has an excellent attenuation coefficient; the first vibration-damping material of the present application can use the high attenuation coefficient characteristics of its material to convert the external mechanical vibration energy into friction heat inside the alloy material and dissipate it under external mechanical vibration (such as friction vibration caused by braking), thereby achieving the effect of vibration reduction and noise reduction.

[0049] In the present application, the mass percentage of the first vibration damping material is "20% to 60%", which means that the minimum and maximum values ​​of the above range can be taken, as well as each value between the minimum and maximum values. Specifically including but not limited to the point values ​​in the embodiment and the following point values: 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59% or 60%.

[0050] In some optional embodiments, the mass percentage of the first vibration damping material is 30%-50%.

[0051] In some embodiments, based on the total mass of the friction material, the first vibration damping material includes 10% to 30% of chrome steel alloy, 5% to 20% of manganese copper alloy, and 5% to 25% of cast iron alloy.

[0052] In some specific embodiments, the mass percentage of chromium in the chromium steel alloy is 10%-15%, and the mass percentage of carbon is 0.05%-0.55%.

[0053] In some optional embodiments, the mass percentage of chromium element in the chromium steel alloy is 12%, and the mass percentage of carbon element is 0.1%.

[0054] In some specific embodiments, the chrome-steel alloy includes one or more of chrome-steel alloy fibers and chrome-steel alloy powders; the length of the chrome-steel alloy fibers is 2 mm to 10 mm, and the particle size of the chrome-steel alloy powder is 0.01 mm to 2 mm.

[0055] In some optional embodiments, the chrome steel alloy fiber is 5 mm in length.

[0056] In some optional embodiments, the particle size of the chromium steel alloy powder is 0.04 mm to 0.15 mm.

[0057] Chromium steel alloy is a ferromagnetic vibration-damping material. Under external friction and vibration, the magnetic domains of the chromium steel alloy material will move and rotate, converting the external mechanical vibration energy into internal heat energy of the material and consuming it, so that the vibration and noise will decay rapidly, thereby reducing vibration and noise.

[0058] In some specific embodiments, the mass percentage of manganese in the manganese-copper alloy is 40% to 80%.

[0059] In some specific embodiments, the manganese-copper alloy includes one or more of manganese-copper alloy fibers and manganese-copper alloy powders; the length of the manganese-copper alloy fibers is 2 mm to 10 mm, and the particle size of the manganese-copper alloy powder is 0.01 mm to 2 mm.

[0060] In some optional embodiments, the mass percentage of manganese element in the manganese-copper alloy fiber is 40%-80%.

[0061] In some optional embodiments, the mass percentage of manganese element in the manganese-copper alloy powder is 40%-60%.

[0062] In some optional embodiments, the mass percentage of manganese element in the manganese-copper alloy is 60%.

[0063] In some optional embodiments, the length of the manganese-copper alloy fiber is 5 mm.

[0064] In some optional embodiments, the particle size of the manganese-copper alloy powder is 0.04 mm to 0.15 mm.

[0065] Manganese-copper alloy is a dislocation type material. When there is external vibration, the interaction between the dislocations and inclusion atoms inside the alloy material can absorb the external vibration energy, thereby reducing vibration and noise.

[0066] In some specific embodiments, the mass percentage of carbon in the cast iron alloy is 2.5% to 4.5%.

[0067] In some optional embodiments, the mass percentage of carbon in the cast iron alloy is 3.5%.

[0068] In some specific embodiments, the cast iron alloy includes one or more of cast iron alloy fibers and cast iron alloy powders; the length of the cast iron alloy fibers is 2 mm to 10 mm, and the particle size of the cast iron alloy powder is 0.01 mm to 2 mm.

[0069] In some optional embodiments, the length of the cast iron alloy fiber is 5 mm.

[0070] In some optional embodiments, the particle size of the cast iron alloy powder is 0.03 mm to 0.15 mm.

[0071] Cast iron alloy is a second-phase vibration-damping material that contains graphite. When external vibration occurs, the cast iron alloy can exert the ability of graphite to plastically deform and convert the vibration energy into internal friction energy of the alloy material, thereby achieving vibration and noise reduction effects.

[0072] In some specific embodiments, the particle size of the spherical aluminum oxide is 0.005 mm to 0.03 mm. As an example, the particle size of the spherical aluminum oxide can be, but is not limited to, specific values ​​such as 0.005 mm, 0.01 mm, 0.02 mm or 0.03 mm.

[0073] In some examples, the content of aluminum oxide in the spherical aluminum oxide is 99.99%.

[0074] In some optional embodiments, the particle size of the spherical alumina is 0.01 mm to 0.15 mm.

[0075] In some optional embodiments, the mass percentage of spherical alumina is 3% to 10%.

[0076] In some specific embodiments, the particle size of zirconium silicate is 0.01 mm to 0.04 mm. As an example, the particle size of zirconium silicate can be, but is not limited to, specific values ​​such as 0.01 mm, 0.02 mm, 0.03 mm or 0.04 mm.

[0077] In some examples, the zirconium content of the zirconium silicate is 65%.

[0078] In some optional embodiments, the particle size of zirconium silicate is 0.015 mm to 0.025 mm.

[0079] In some optional embodiments, the mass percentage of zirconium silicate is 5% to 15%.

[0080] In some specific embodiments, the particle size of stannous sulfide is 0.01 mm to 0.061 mm. As an example, the particle size of stannous sulfide can be, but is not limited to, specific values ​​such as 0.01 mm, 0.02 mm, 0.03 mm, 0.04 mm, 0.05 mm or 0.06 mm.

[0081] In some examples, the tin content of stannous sulfide is 60% to 80%; alternatively, the tin content is 72% to 75%.

[0082] In some optional embodiments, the particle size of stannous sulfide is 0.019 mm to 0.053 mm.

[0083] In some optional embodiments, the mass percentage of stannous sulfide is 5% to 8%.

[0084] In some specific embodiments, the particle size of the chromite is 0.019 mm to 0.089 mm. As an example, the particle size of the chromite can be, but is not limited to, specific values ​​such as 0.019 mm, 0.02 mm, 0.03 mm, 0.04 mm, 0.05 mm, 0.06 mm, 0.07 mm, 0.08 mm or 0.089 mm.

[0085] In some examples, the chromium content of the chromite is 44%.

[0086] In some optional embodiments, the particle size of the chromite is 0.03 mm to 0.061 mm.

[0087] In some optional embodiments, the mass percentage of chromite is 5% to 12%.

[0088] In the present application, the mass percentage of the second vibration damping material is "8% to 29%", which means that the minimum and maximum values ​​of the above range can be taken, as well as each value between the minimum and maximum values. Specifically including but not limited to the point values ​​in the embodiment and the following point values: 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28% or 29%.

[0089] In some optional embodiments, the mass percentage of the second vibration damping material is 10%-15%.

[0090] In some embodiments, based on the total mass of the friction material, the second vibration damping material includes 3% to 9% vermiculite and 5% to 20% porous graphite.

[0091] In some specific embodiments, the particle size of vermiculite is 0.15 mm to 4 mm. As an example, the particle size of chromite can be, but is not limited to, specific values ​​such as 0.015 mm, 0.05 mm, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm or 4 mm.

[0092] In some optional embodiments, the particle size of the vermiculite is 0.5 mm to 2 mm.

[0093] In some specific embodiments, the particle size of the porous graphite is 0.038 mm to 0.5 mm. As an example, the particle size of chromite can be, but is not limited to, specific values ​​such as 0.038 mm, 0.05 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm or 0.5 mm.

[0094] In some optional embodiments, the particle size of the porous graphite is 0.074 mm to 0.15 mm.

[0095] Vermiculite and porous graphite are both inorganic materials with porous structures, which can effectively absorb brake vibration and noise, thereby reducing brake noise. During the braking vibration process, the layered porous structure of vermiculite can consume vibration energy and absorb brake noise through microscopic deformation of the layer spacing under braking pressure.

[0096] Porous graphite itself has the characteristics of low hardness, lubrication and noise reduction. It also contains open and closed pore microporous structures. During the braking process, the microporous structure absorbs and dissipates vibration energy, which can reduce the occurrence of vibration noise.

[0097] At the same time, under high temperature conditions, the layered porous structure of vermiculite and the surface pores of porous graphite can absorb small molecular products such as carbon dioxide, ammonia, and water vapor produced by the decomposition of phenolic resin, reducing the decrease in friction coefficient (i.e. thermal decay) caused by the air cushion phenomenon on the friction surfaces, thereby effectively stabilizing the high-temperature friction coefficient of the friction material.

[0098] In some embodiments, the adhesive includes one or more of phenolic resin, rubber-modified phenolic resin, phosphorus-modified phenolic resin, silicon-modified phenolic resin, and cashew nut shell oil-modified phenolic resin.

[0099] In some optional embodiments, the mass percentage of the adhesive is 12% to 18%.

[0100] The friction material prepared by using the above-mentioned specific materials has the advantages of vibration reduction and noise reduction, and has no decay phenomenon under high temperature conditions.

[0101] Some embodiments of the present application provide a brake friction pad comprising the above-mentioned friction material.

[0102] The brake friction pad containing the above-mentioned friction material can reduce the noise generated during braking with the carbon-ceramic coated brake disc and improve the riding comfort.

[0103] Some embodiments of the present application provide a method for preparing a friction brake pad, comprising S10 to S30:

[0104] S10: providing various raw materials according to the components of the friction material of the first aspect, mixing them, and obtaining a mixture;

[0105] S20: stacking the mixed material and the steel backing, and forming a brake pad blank by hot pressing;

[0106] S30: performing curing treatment, shape processing treatment and assembly treatment on the brake pad blank in sequence to obtain a brake friction brake pad.

[0107] In some specific embodiments, the mixing method in S10 is adding into a plowshare mixer for mixing; wherein the speed of the mixing spindle is 200 rpm, the speed of the plowshare is 3000 rpm, and the mixing time is 15 minutes.

[0108] In some specific embodiments, the pressing pressure per unit area of ​​the hot pressing molding in S20 is 15 MPa to 60 MPa.

[0109] In some examples, the pressing pressure per unit area of ​​the hot pressing molding in S20 is 25 MPa to 50 MPa.

[0110] In some specific embodiments, the temperature of the hot pressing molding in S20 is 140° C. to 170° C.

[0111] In some examples, the temperature of the hot pressing molding in S20 is 150° C. to 160° C.

[0112] In some examples, the exhaust gas procedure is: pressurize for 20 seconds - release and exhaust for 5 seconds - pressurize for 20 seconds - release and exhaust for 5 seconds - pressurize for 20 seconds - release and exhaust for 5 seconds - pressurize for 150 seconds.

[0113] In some specific embodiments, the curing treatment in S30 is performed at a temperature of 200° C. to 240° C. and for a time of 9 h to 11 h.

[0114] In some examples, the shape processing in S30 includes: performing rough grinding, grooving, left chamfering, right chamfering, and fine grinding on the heat-treated brake pad blank in sequence according to the design drawing on a grinder.

[0115] In some examples, the assembly process in S30 includes riveting silencers, alarms, springs, inkjet printing, etc.

[0116] In some examples, after the shape processing in S30 and before the assembly, the following steps are also included: infrared ablation treatment and electrostatic spraying of plastic powder on the brake pad blank.

[0117] Some embodiments of the present application provide a brake friction pair, comprising the above-mentioned brake friction brake pad and a silicon carbide coated brake disc.

[0118] The above-mentioned brake friction pair can effectively alleviate the problem of brake noise easily generated by carbon-ceramic coated brake discs during braking.

[0119] Some embodiments of the present application provide at least one of the above-mentioned brake pad and the above-mentioned carbon-ceramic friction pair.

[0120] It can be understood that the means of transportation include but are not limited to cars, sports cars, racing cars, airplanes, high-speed trains, subways, etc.

[0121] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.

[0122] Example 1

[0123] (1) Provide the following raw materials in percentage by mass: 15% chrome steel alloy fiber, 15% manganese copper alloy fiber, 5% cast iron alloy fiber, 5% cast iron alloy powder, 3% vermiculite, 12% porous graphite, 12% phenolic resin, 8% spherical alumina, 8% zirconium silicate, 8% stannous sulfide and 9% chromite. Add the above raw materials together into a plowshare mixer and mix to obtain a mixture. The mixing spindle speed is 200 rpm, the plowshare speed is 3000 rpm, and the mixing time is 15 minutes.

[0124] The mass percentage of chromium in the chromium steel alloy fiber is 12%, the mass percentage of carbon is 0.1%, and the fiber length is 5 mm;

[0125] The mass percentage of manganese in the manganese-copper alloy is 60%, and the fiber length is 5 mm;

[0126] The mass percentage of carbon in the cast iron alloy fiber is 3.5%, and the fiber length is 5 mm;

[0127] The mass percentage of carbon in the cast iron alloy powder is 3.5%, and the powder particle size is 0.035 mm;

[0128] The particle size of vermiculite particles is 0.5 mm;

[0129] The mass percentage of carbon in porous graphite is 99.99% and the particle size is 0.074mm;

[0130] The mass percentage of aluminum oxide in spherical aluminum oxide is 99.99% and the particle size is 0.015 mm;

[0131] The mass percentage of zirconium in zirconium silicate is 66% and the particle size is 0.025 mm;

[0132] The mass percentage of tin in stannous sulfide is 72% and the particle size is 0.053 mm;

[0133] The mass percentage of chromium in chromite is 44% and the particle size is 0.03mm.

[0134] (2) The mixed material obtained in step (1) is composite-formed with the glue-coated steel back on a constant pressure hot press to obtain a brake pad blank.

[0135] The pressing pressure per unit area is 35 MPa, the hot pressing molding temperature is 150°C, and the exhaust gas procedure is: pressurizing and pressing for 20 seconds - pressure relief and exhaust for 5 seconds - pressurizing and pressing for 20 seconds - pressure relief and exhaust for 5 seconds - pressurizing and pressing for 20 seconds - pressure relief and exhaust for 5 seconds - pressurizing and pressing for 150 seconds.

[0136] (3) The brake pad blank obtained in step (2) is subjected to sufficient heat treatment and curing of phenolic resin in a program-controlled temperature curing furnace. The total curing time is 10 hours and the maximum curing temperature is 240°C.

[0137] (4) The heat-treated brake pad blank is processed on a grinder according to the design drawings through rough grinding, grooving, left chamfering, right chamfering, and fine grinding. The processed brake pad is also subjected to infrared ablation, electrostatic spraying of plastic powder, riveting of silencers, alarms, springs, and coding and printing processes to obtain a brake friction brake pad suitable for a carbon-ceramic coated brake disc.

[0138] Example 2

[0139] The method is basically the same as Example 1, except that the raw materials in step (1) are different: the mass percentage of the first vibration damping material is 60%; the mass percentages of the remaining components are as shown in Table 1.

[0140] Example 3

[0141] The method is basically the same as Example 1, except that the raw materials in step (1) are different: the mass percentage of the first vibration damping material is 20%; the mass percentages of the remaining components are as shown in Table 1.

[0142] Example 4

[0143] The method is basically the same as Example 1, except that the raw materials in step (1) are different: the mass percentage of the first vibration-damping material is 45%; the mass percentages of the remaining components are as shown in Table 1.

[0144] Example 5

[0145] The method is basically the same as Example 1, except that the raw materials in step (1) are different: the mass percentage of the second vibration damping material is 8%; the mass percentages of the remaining components are shown in Table 1.

[0146] Comparative Example 1

[0147] The method is basically the same as Example 1, except that the raw materials in step (1) are different: only 40% of chromium steel alloy fiber is used as the first vibration damping material, and no manganese copper alloy and cast iron alloy are added.

[0148] Comparative Example 2

[0149] The method is basically the same as Example 1, except that the raw materials in step (1) are different: only 40% of manganese-copper alloy fiber is used as the first vibration damping material, and no chromium steel alloy and cast iron alloy are added.

[0150] Comparative Example 3

[0151] The method is basically the same as Example 1, except that the raw materials in step (1) are different: only 40% of cast iron alloy fiber is used as the first vibration damping material, and no chromium steel alloy, manganese copper alloy and cast iron alloy powder are added.

[0152] Comparative Example 4

[0153] The method is basically the same as Example 1, except that the raw materials in step (1) are different: only 15% of vermiculite is used as the second vibration damping material, and no porous graphite is added.

[0154] Comparative Example 5

[0155] The method is basically the same as Example 1, except that the raw materials in step (1) are different: only 15% of porous graphite is used as the second vibration damping material, and no vermiculite is added.

[0156] The raw material components of the friction materials in the above-mentioned Examples 1 to 5 are shown in Table 1; the raw material components of the friction materials in Comparative Examples 1 to 5 are shown in Table 2.

[0157] Table 1

[0158]

[0159] Table 2

[0160]

[0161] The physical property tests were performed on the friction brake pads prepared in the above Examples 1 to 5 and Comparative Examples 1 to 5. Specifically, the density test was performed by the drainage method according to the GB / T1463-2005 standard, the internal shear strength test was performed according to the GB / T 26739-2011 standard, and the product compression test was performed according to the SAE J 2522 standard. The results are shown in Table 3.

[0162] Table 3

[0163]

[0164] As shown in Table 3, the present invention selects chrome steel alloy, manganese copper alloy, cast iron alloy, vermiculite and porous graphite as raw materials for preparing friction materials, and the density of the brake pads finally prepared is less than 3.5 g / cm 3 The average internal shear strength is greater than 5MPa, and the average compression rate is between 97μm and 114μm, which fully meets the needs of practical applications.

[0165] The brake friction pads prepared in the above Examples 1 to 5 and Comparative Examples 1 to 5 were combined with a carbon-ceramic coated brake disc with a diameter of 380 mm to form a carbon-ceramic friction pair. Noise characteristics were tested on a Link3900 inertia test bench according to the SAE J2521 standard. The results are shown in Table 4.

[0166] Table 4

[0167]

[0168] It can be seen from Table 4 that in the noise test, the brake pads prepared in Examples 1 to 5 of the present application have a probability of noise greater than 70db of 1.5% to 2.2%, which is much lower than the probability of high-decibel noise in Comparative Examples 1 to 5.

[0169] The friction coefficient and wear rate of the brake pads prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were measured at different braking temperatures, speeds and pressures according to the SAE J2522 standard, and the results are shown in Table 5. Among them, high temperature decay (1) and (2) refer to the minimum friction coefficient when the braking temperature exceeds 500°C in the SAE J2522 standard.

[0170] Table 5

[0171]

[0172] It can be seen from Table 5 that the brake pads prepared in Examples 1 to 5 of the present application have a high friction coefficient at different initial braking speeds and are relatively stable at different braking speeds; they still have a high friction coefficient under high temperature test conditions; and the thickness wear is less than 0.5 mm.

[0173] Comparative Examples 1 to 5 use a single first damping material or a single second damping material to prepare the friction material, and one or more aspects of the physical and chemical properties, noise test, friction coefficient or wear test of the final brake pads cannot meet the technical requirements.

[0174] Specifically, in Comparative Example 1, the first vibration damping material only contains chromium steel alloy, and the noise occurrence probability of the finally produced brake pad is 4.8%, which cannot meet the technical requirements. In Comparative Example 2, the first vibration damping material only contains manganese copper alloy, and the internal shear strength of the finally produced brake pad is lower than 5MPa, and the noise occurrence probability is 3.7%, which cannot meet the technical requirements. In Comparative Example 3, the first vibration damping material only contains cast iron alloy, and the noise occurrence probability of the finally produced brake pad is 5.4%, which cannot meet the technical requirements. In Comparative Example 4, the second vibration damping material only contains vermiculite, and the internal shear strength of the finally produced brake pad is lower than 5MPa, the compression rate reaches 130μm, and the noise occurrence probability is 3.5%, which cannot meet the technical requirements. In Comparative Example 5, the second vibration damping material only contains porous graphite, and the noise occurrence probability of the finally produced brake pad is 4.9%, which cannot meet the technical requirements.

[0175] In addition, the friction coefficient decreased and the wear increased in Comparative Examples 1 to 5. For example, the overall friction coefficient of the brake pads in Comparative Examples 4 and 5 decreased to below 0.40, while the friction coefficient of Comparative Examples 1 to 3 was lower than 0.40 under high-speed tests. At the same time, it was found in the friction test that the average thickness of the brake pad in Comparative Example 4 was worn to 1.25 mm, which greatly exceeded the technical requirements.

[0176] The friction material made of multiple first vibration-damping materials and multiple second vibration-damping materials in Examples 1 to 5 of the present application is used to make brake pads, which have excellent physical and chemical properties, friction coefficients or wear data. When tested in combination with carbon-ceramic coated brake discs, the probability of noise greater than 70 dB is greatly reduced.

[0177] The above results show that the brake pad made of the friction material of the present application has excellent vibration reduction and noise reduction performance, and at the same time, its friction coefficient is high and stable, and the wear during use is small, and it can be applied to carbon-ceramic coated brake discs with higher hardness.

[0178] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0179] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A friction material, characterized in that: The composition comprises the following components by mass percentage: 20% to 60% of a first vibration damping material, 8% to 29% of a second vibration damping material, 10% to 20% of an adhesive, 3% to 15% of spherical alumina, 3% to 20% of zirconium silicate, 3% to 10% of stannous sulfide and 3% to 15% of chromite; Wherein, based on the total mass of the friction material, the first vibration damping material includes 10% to 30% chromium steel alloy, 5% to 20% manganese copper alloy and 5% to 25% cast iron alloy; the second vibration damping material includes 3% to 9% vermiculite and 5% to 20% porous graphite.

2. The friction material according to claim 1, characterized in that: The mass percentage of chromium element in the chromium steel alloy is 10% to 15%, and the mass percentage of carbon element is 0.05% to 0.55%.

3. The friction material according to claim 1, characterized in that: The chrome-steel alloy comprises one or more of chrome-steel alloy fibers and chrome-steel alloy powders; the length of the chrome-steel alloy fibers is 2 mm to 10 mm, and the particle size of the chrome-steel alloy powder is 0.01 mm to 2 mm.

4. The friction material according to claim 1, characterized in that: The mass percentage of manganese element in the manganese-copper alloy is 40% to 80%.

5. The friction material according to claim 1, characterized in that: The manganese-copper alloy includes one or more of manganese-copper alloy fibers and manganese-copper alloy powders; the length of the manganese-copper alloy fibers is 2 mm to 10 mm, and the particle size of the manganese-copper alloy powder is 0.01 mm to 2 mm.

6. The friction material according to claim 1, characterized in that: The mass percentage of carbon element in the cast iron alloy is 2.5% to 4.5%.

7. The friction material according to claim 1, characterized in that: The cast iron alloy comprises one or more of cast iron alloy fibers and cast iron alloy powders; the length of the cast iron alloy fibers is 2 mm to 10 mm, and the particle size of the cast iron alloy powder is 0.01 mm to 2 mm.

8. The friction material according to claim 1, characterized in that: The particle size of the spherical alumina is 0.005 mm to 0.03 mm.

9. The friction material according to claim 1, characterized in that: The particle size of the zirconium silicate is 0.01 mm to 0.04 mm.

10. The friction material according to claim 1, characterized in that: The particle size of the stannous sulfide is 0.01 mm to 0.061 mm.

11. The friction material according to claim 1, characterized in that: The particle size of the chromite is 0.019 mm to 0.089 mm.

12. The friction material according to claim 1, characterized in that: The particle size of the vermiculite is 0.15 mm to 4 mm.

13. The friction material according to claim 1, characterized in that: The particle size of the porous graphite is 0.038 mm to 0.5 mm.

14. The friction material according to claim 1, characterized in that: The adhesive includes one or more of phenolic resin, rubber-modified phenolic resin, phosphorus-modified phenolic resin, silicon-modified phenolic resin and cashew nut shell oil-modified phenolic resin.

15. A friction brake pad, characterized in that: The friction material comprises the friction material according to any one of claims 1 to 14.

16. A method for preparing a friction brake pad, characterized in that: The steps include: Providing raw materials according to the components of the friction material according to any one of claims 1 to 14, mixing them to obtain a mixture; The mixed material is stacked with a steel backing, and a brake pad blank is obtained by hot pressing; The brake pad blank is subjected to curing treatment, shape processing treatment and assembly treatment in sequence to obtain a brake friction brake pad.

17. The method for preparing a friction brake pad according to claim 16, characterized in that: The preparation method meets at least one of the following characteristics: (1) The pressing pressure per unit area of ​​hot pressing is 15MPa~60MPa; (2) The temperature of hot pressing is 140℃~170℃; (3) The curing temperature is 200℃~240℃ and the curing time is 9h~11h.

18. A brake friction pair, characterized in that: It is characterized in that The invention comprises the brake friction pad as claimed in claim 15 and a silicon carbide coated brake disc.

Citation Information

Patent Citations

  • Friction material, brake pad made thereof and method for manufacturing brake pad

    CN108916276A

Cited By

  • Brake pad friction material, brake pad and preparation method of brake pad

    CN121652535A